2021
DOI: 10.1021/jacs.1c07798
|View full text |Cite
|
Sign up to set email alerts
|

Surface Glycan Modification of Cellular Nanosponges to Promote SARS-CoV-2 Inhibition

Abstract: Cellular binding and entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are mediated by its spike glycoprotein (S protein), which binds with not only the human angiotensin-converting enzyme 2 (ACE2) receptor but also glycosaminoglycans such as heparin. Cell membrane-coated nanoparticles (“cellular nanosponges”) mimic the host cells to attract and neutralize SARS-CoV-2 through natural cellular receptors, leading to a broad-spectrum antiviral strategy. Herein, we show that increasing surface h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…The severity of COVID-19 is associated with the SARS-CoV-2 load, and the activation of host inflammatory responses. For this reason, mitigating the inflammatory response is critical to develop anti-SARS-CoV-2 therapies 63 . NF-κB signaling has been implicated as a key pathway underlying COVID-19-associated inflammation 15 , and we recently revealed the important role of IKKβ, a central inflammatory coordinator through activating NF-κB, in the regulation of other viral protein (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of COVID-19 is associated with the SARS-CoV-2 load, and the activation of host inflammatory responses. For this reason, mitigating the inflammatory response is critical to develop anti-SARS-CoV-2 therapies 63 . NF-κB signaling has been implicated as a key pathway underlying COVID-19-associated inflammation 15 , and we recently revealed the important role of IKKβ, a central inflammatory coordinator through activating NF-κB, in the regulation of other viral protein (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the designed system attaching both the virus and cytokines exhibited better antiviral capacity than the nanovesicles obtained from 293T/ACE2 alone [ 92 ]. Recently, THP-1 membrane-derived PLGA NPs of approximatively 100 nm were also evaluated for their SARS-CoV-2 inhibition, but the main focus was the effect of surface modification of the nanosponges with heparin on the virus neutralization [ 93 ]. However, the potency of THP-1 mimetics of cytokines neutralization shouldn’t be disregarded.…”
Section: Implications Of Inflammation In Covid-19 Therapies and Drug ...mentioning
confidence: 99%
“…However, the potency of THP-1 mimetics of cytokines neutralization shouldn’t be disregarded. Fluorescence spectra using labeled antibodies, such as anti-CD130, anti-CD120a, and anti-CD119 receptors (for IL-6, TNF- α , and IFN- γ , respectively) showed that the surface modification didn’t alter the ability of the monocytes to trap cytokines [ 93 ].…”
Section: Implications Of Inflammation In Covid-19 Therapies and Drug ...mentioning
confidence: 99%
“…Cellular nanosponges composed of polymer cores and cell membranes could simulate host cells, attract, and neutralize SARS‐CoV‐2 through natural cell receptors, thereby generating a broad‐spectrum antiviral strategy 121 . The further increasing of the surface heparin concentration on the cellular nanosponges could promote its inhibitory effect on SARS‐CoV‐2 126 . As the vector of antiviral drugs, nanomaterials cannot only control the release of drugs, but also decrease the side effects by targeted delivery 117,118 …”
Section: Perspectives and Current Challengesmentioning
confidence: 99%
“…121 The further increasing of the surface heparin concentration on the cellular nanosponges could promote its inhibitory effect on SARS-CoV-2. 126 As the vector of antiviral drugs, nanomaterials cannot only control the release of drugs, but also decrease the side effects by targeted delivery. 117,118 We can see the successes of nanotechnology-based strategy from detecting, preventing to treating the SARS-CoV-2.…”
Section: Perspectives and Current Challengesmentioning
confidence: 99%